The Impact of Regional Trade and Global Financial Crisis on Small and Medium-Sized Enterprise Support Policy in Japan - Buczkowski, Bogdan (Wpływ współpracy regionalnej i globalnego kryzysu finansowego na politykę wspierania małych i średnich przedsiębiorstw w Japonii, 2010)
The financial crisis, which caused the collapse in the economy and had a significant impact on SMEs in Japan, differs from the past financial crises. It touched more export-oriented economies than domestic-demand-oriented ones. Automotive and financial companies suffered more than those in sectors less dependent on economic cycle. Japan greatly benefited from the boom in Asian countries, including China, India and Korea. The challenge now is a decline in global demand for cars and electronics, primarily in Europe and the U.S and the progress and increase of the competitiveness of those industries, together with the development of healthcare, environmental technologies and tourism in Asian countries, in particular in China. Greater regional integration could help in the internationalization of weak industries by encouraging foreign investment and increasing competition on the domestic market.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 379-386
Keywords: financial crisis; Japaniese business